Macbeth multiplied : negotiating historical and medial difference between Shakespeare and Verdi - Clausen, Christoph (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2005)
In what sense did Shakespeare's representation of the Weird Sisters participate in the rewriting of village witchcraft? Was it likely to "encourage the Sword"? Did opera's specific medial conditions offer Verdi special opportunities to justify the presence of stage witches more than three centuries later? How valid is the parallel between 19th century opera and the voyeurism of madhouse spectacle? Was Shakespeare's play really engaged in the project of exorcizing Queen Elizabeth's cultural memory? What does Verdi's chorus of Scottish refugees have to do with shifting representations of 'the pe.